2016
DOI: 10.3389/fmicb.2016.01888
|View full text |Cite
|
Sign up to set email alerts
|

An Essential Factor for High Mg2+ Tolerance of Staphylococcus aureus

Abstract: Internal bacterial concentration of Mg2+, the most abundant divalent cation in living cells, is estimated to be in the single millimolar range. However, many bacteria will thrive in media with only micromolars of Mg2+, by using a range of intensely studied and highly efficient import mechanisms, as well as in media with very high magnesium concentration, presumably mediated by currently unknown export mechanisms. Staphylococcus aureus has a particularly high Mg2+ tolerance for a pathogen, growing unimpaired in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(69 citation statements)
references
References 39 publications
2
67
0
Order By: Relevance
“…Heterologous expression of the LP965 and EF.A CorC proteins in L. casei also confirmed the importance of the single G334V point mutation in conferring PlnEF resistance. Because we did not find other mutants and because we were unable to construct a CorC deletion mutant in either LP965 or LP8826, our results indicate that similar to S. aureus MpfA (Armitano et al, 2016), CorC is essential for maintaining magnesium metal homeostasis in L. plantarum.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Heterologous expression of the LP965 and EF.A CorC proteins in L. casei also confirmed the importance of the single G334V point mutation in conferring PlnEF resistance. Because we did not find other mutants and because we were unable to construct a CorC deletion mutant in either LP965 or LP8826, our results indicate that similar to S. aureus MpfA (Armitano et al, 2016), CorC is essential for maintaining magnesium metal homeostasis in L. plantarum.…”
Section: Discussionmentioning
confidence: 87%
“…In eukaryotes, the cyclin M (CNNM) family of proteins mediate Mg 2+ transport and share some structural similarities to bacterial CorC and CorB including the C-terminal CBS pairs (Hirata, Funato, Takano, & Miki, 2014). The CBS domains of magnesium transporters are reported to be important for magnesium and ATP binding (Armitano, Redder, Guimarães, & Linder, 2016;Baykov et al, 2011). Recently, a Staphylococcus aureus protein with a domain structure similar to Salmonella CorB (magnesium protection factor A (MpfA); SA00657) was found to be essential for S. aureus growth in magnesium concentrations as low as 10 mM (Armitano et al, 2016) (Zhang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides these direct measurements of [Mg 2+ ] i or total Mg levels, it was recently reported that Staphylococcus aureus with mutations in the Cnnm orthologue, MpfA , were intolerant to high levels of Mg 2+ in the culture medium (Armitano et al . ), suggesting that [Mg 2+ ] i is increased in the MpfA mutants. Taken together with the observations described in the previous paragraph, all these results support the concept that CNNM reduces intracellular Mg 2+ levels.…”
Section: Mg2+ Decrease By Overexpression Of Cnnmmentioning
confidence: 95%
“…There, an ATP bound Mg 2+ cation reduces the electrostatic repulsion between its polyphosphate chain and the acidic cluster. Interestingly, this acidic cluster not only appears in the CNNMs but also in other CBS-containing proteins related with Mg 2+ extrusion such as the Mg 2+ tolerance factor SA0657 found in Staphylococcus aureus [43], or bacterial proteins CorB and CorC which have been proposed to mediate Mg 2+ extrusion through bacterial Mg 2+ channel CorA [44] (Supplementary Figure S1). In other CBS-containing proteins such as the bacterial Mg 2+ channel MgtE [45,46] or the chloride channels CLCs [47], this acidic cluster is substituted by positively charged residues, which favor the interaction with the triphosphate chain of ATP.…”
Section: Crystal Structure Of Cnnm4 Batmentioning
confidence: 99%